Environmentally induced crack (EIC) initiation, propagation, and failure: A 3D in-situ time-lapse study of AA5083 H131. (September 2020) - Gudla, Visweswara Chakravarthy; Storm, Malte; Palmer, Benjamin C.; Lewandowski, John J.; Withers, Philip J.; Holroyd, N.J. Henry; Burnett, Timothy L.
Graphical abstract: Highlights: Entire colonies of environmentally induced cracks have been observed in 4D. Cracks initiate continuously from 0.5σy until failure; the rate is highest under straining. EIC cracks clearly propagate below KIEIC threshold but are susceptible to arrest. Propagation of all cracks is discontinuous and ranges from 0 to 20x the average velocity. Microstructural obstacles can be directly related to the propagation behaviour. Abstract: Environment Induced Cracking (EIC) has been observed in three dimensions (3D) at high spatial and temporal resolution for AA5083 H131 alloy using in situ synchrotron X-ray CT. The initiation of EIC cracks occurred in humid air at ∼0.5σy and started from corrosion sites associated with intermetallic particle clusters. Time-resolved monitoring of the crack growth confirmed cracks grow below threshold KIEIC and are susceptible to arrest under fixed displacement conditions. Even when the cracks exceed threshold KIEIC and enter sustained propagation they exhibit very uneven growth rates. Failure occurs when the K of the largest crack exceeds the fracture toughness KIC .